2016
DOI: 10.1128/jb.00020-16
|View full text |Cite
|
Sign up to set email alerts
|

Azospirillum brasilense Chemotaxis Depends on Two Signaling Pathways Regulating Distinct Motility Parameters

Abstract: The genomes of most motile bacteria encode two or more chemotaxis (Che) systems, but their functions have been characterized in only a few model systems. Azospirillum brasilense is a motile soil alphaproteobacterium able to colonize the rhizosphere of cereals. In response to an attractant, motile A. brasilense cells transiently increase swimming speed and suppress reversals. The Che1 chemotaxis pathway was previously shown to regulate changes in the swimming speed, but it has a minor role in chemotaxis and roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 45 publications
5
52
0
Order By: Relevance
“…Specifically, we identify the binding of c-di-GMP to particular receptors as a mechanism to modulate the contribution of these receptors to the aerotaxis signaling output. Therefore, A. brasilense aerotaxis depends not only on signaling by dedicated chemotaxis receptors (5,26,30), as expected, but also on intracellular c-di-GMP levels.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Specifically, we identify the binding of c-di-GMP to particular receptors as a mechanism to modulate the contribution of these receptors to the aerotaxis signaling output. Therefore, A. brasilense aerotaxis depends not only on signaling by dedicated chemotaxis receptors (5,26,30), as expected, but also on intracellular c-di-GMP levels.…”
Section: Discussionmentioning
confidence: 96%
“…A. brasilense cells respond tactically to oxygen gradients via signaling by two Che systems that coordinately control transient changes in the swimming speed and in the probability of swimming reversals (25,26). Therefore, we next examined the effect of transient changes in intracellular c-di-GMP levels on these motility parameters under steady-state conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Cells attach to plant roots through a two-step process (32), a rapid reversible adsorption, thought to be mediated by the polar flagellum, and a slow irreversible anchoring, thought to be mediated by an as-yet unidentified surface polysaccharide (33). A recent study reported that mutants in components of the Che4 chemotaxis system are defective in this root colonization (34). A. brasilense cells also attach to conspecifics in the presence of elevated oxygen levels (35).…”
Section: Resultsmentioning
confidence: 99%
“…However, deletion of che1 or of the gene for the histidine kinase of the Che1 pathway, cheA1, has a minor effect on chemotaxis (17). An additional Che pathway, which has a more dominant role in controlling chemotaxis, has recently been identified (19). In addition to regulating transient increases in swimming speed, Che1 is implicated in regulating cell length: mutations that render cheA1, che1, or cheY1 nonfunctional also result in cells of relatively shorter lengths than the wild type, while mutations that abolish the function of enzymes required for chemotaxis receptor adaptation, CheB1 and CheR1, result in cells significantly longer than the wild type, with these effects most evident in dividing cells (17).…”
mentioning
confidence: 99%